Lack of agreement between optimal mean arterial pressure determination using pressure reactivity index versus cerebral oximetry index in hypoxic ischemic brain injury after cardiac arrest. (July 2020) - Hoiland, Ryan L.; Sekhon, Mypinder S.; Cardim, Danilo; Wood, Michael D.; Gooderham, Peter; Foster, Denise; Griesdale, Donald E.
Abstract: Introduction: Invasive monitoring of cerebral autoregulation using the pressure reactivity index (PRx) allows for the determination of optimal mean arterial pressure (MAPOPT ) in hypoxic ischemic brain injury (HIBI) patients following cardiac arrest. However, the utility of non-invasive surrogates to determine MAPOPT has not been addressed. We aimed to determine the agreement between PRx-derived MAPOPT versus MAPOPT determined by the near-infrared spectroscopy (NIRS) based cerebral oximetry index (COx). Methods: Ten HIBI patients were enrolled. PRx-derived MAPOPT, lower (LLA) and upper limits of autoregulation (ULA) were compared against COx-derived MAPOPT, LLA and ULA. Multimodal neuromonitoring included mean arterial pressure, intracranial pressure, brain tissue oxygenation, jugular venous oxygen saturation, and NIRS-derived regional cerebral oxygen saturation. Results: Repeated measures Bland–Altman plots demonstrated limited agreement between MAPOPT derived from COx and PRx (mean bias: 1.4 mmHg; upper limit of agreement: 25.9 mmHg; lower limit of agreement: −23.0 mmHg). Similarly, there was limited agreement between the absolute values of PRx and COx. Mean bias was 0.26 and the upper and lower limits of agreement were 1.05 and −0.53, respectively. Systematic bias was apparent, whereby at low PRx values COx overestimated PRx and at high PRx values, COx underestimated PRx. COx was limited in its ability to determine impaired autoregulation defined by PRx (receiver operator characteristic area under the curve was 0.488). Conclusion: Collectively, we demonstrate that COx-based determination of MAPOPT lacks agreement with MAPOPT derived from PRx. Further research must be done to evaluate the physiologic and clinical efficacy of PRx derived MAPOPT in HIBI.